â€œAn Evolving Banking e-Services & its Impact on Indian Usersâ€ - Dr. Mini Jain (International Journal of Modern Agriculture, 2020)
Information technology is taken into account because the vital driver for the changes happening round the creation and within the future enlargement of monetary services and banking is one among the foremost significant between them. With the rapid climb of the web most banks are trying to draw in and retain customers during this highly competitive market through providing various e-banking services. Electronic banking service is gradually important in providing customers with a suitable and interactive facility. The target of this study is to explore factors like reduced cost of deal processing, improved payment efficiency, suitability, ease usage, improved banker customer link, less transaction time, consciousness and access to internet facility that shape the customer decision in adoption of e-banking service and to see the customerâ€™s level of satisfaction with reference to electronic banking services provided by Indian banks. The purchasers consuming banking services with the various e-channels are more satisfied but the shortage of alertness and safety may be a major issue within the spread of e-banking services. The paper also aims to look at the present status of banking e-services, identity its strengths and weaknesses, and use the findings in formulating future recommendations to form a contribution to knowledge within the chosen area. The paper concludes with suggestion to form e-banking services simpler within the future.